'Hope for safe prenatal gene tests'. A content analysis of how the UK press media are reporting advances in non‐invasive prenatal testing. (22nd September 2014) - Lewis, Celine; Choudhury, Mahrufa; Chitty, Lyn S.
Abstract Objective To investigate how non‐invasive prenatal testing (NIPT) is portrayed in the UK press media. Methods Content analysis of the ten most widely circulated print/digital news sources in the UK. Results Seventy‐nine articles were identified focusing on NIPT for Down syndrome (n = 67) including single gene disorders (n = 5), whole genome sequencing (n = 8), NIPT technology (n = 2), Rhesus D (n = 1) and fetal sex determination (n = 1). The majority (63%) were in 'serious' papers. Test attributes were frequently cited (100%), in particular that NIPT is a blood test (89%) and avoids risk of miscarriage (56%). The main psychosocial benefit reported was increased time for decision‐making (15%). Concerns were discussed less frequently than benefits (39%), with increase in termination rates the main concern raised (23%). The majority of headlines (52%) projected a positive frame towards NIPT. Regarding overall framing of articles, over two thirds (68%) presented benefits and concerns or limitations; however, only a third (35%) were considered 'balanced'. Conclusion Positive reporting of NIPT in the UK news media reflects the publics' broadly optimistic view towards genomic technology and prenatal testing. Health professionals should be aware that women may have incomplete information or misunderstandings about NIPT. Pre‐test counselling to ensure informed decision‐making is therefore important. © 2014 John Wiley & Sons, Ltd.